Extended Spectrum Beta-Lactamase (ESBL) Produced by Gram-Negative Bacteria in Trinidad and Tobago. (24th August 2021) - Akpaka, Patrick Eberechi; Vaillant, Angel; Wilson, Clyde; Jayaratne, Padman
Abstract : Gram-negative bacterial infections are a global health problem. The production of beta-lactamase is still the most vital factor leading to beta-lactam resistance. In Trinidad and Tobago, extended spectrum beta-lactamase (ESBL) production has been detected and reported mainly in the isolates of Klebsiella pneumoniae and Escherichia coli and constitutes a public health emergency that causes high morbidity and mortality in some patients. In this literature review, the authors cover vast information on ESBL frequency and laboratory detection using both conventional and molecular methods from clinical data. The aim is to make the reader reflect on how the actual knowledge can be used for rapid detection and understanding of the spread of antimicrobial resistance problems stemming from ESBL production among common Gram-negative organisms in the health care system.